The Post Genomic Era: Novel approaches for studying plant diseases and their management - P. UMADEVI, M. ANANDARAJ* and (Indian Phytopathology, 2016)
Plant pathologists the world over are racing with plant pathogens to deploy resistance genes but pathogens continue to cause about 15% crops loss. Hence protecting crops from devastating pathogens is a continuous challenge to plant pathologists. Understanding host pathogen interactions and the molecular arms race between pathogens and their host plant has been the task of plant pathologists. The advancements in sequencing techniques, computational biology have helped to a greater understanding of the molecular events during pathogenesis. The science of omics -transcriptomics, proteomics, ionomics and metabolomics in the post genomic era have provided opportunities to understand the interaction well. In this review transcriptomics and proteomics in understanding the mechanisms of resistance in Piper colubrinum and P. nigrum to P. capsici and Curcuma amada and Zingiber officinale to Ralstonia soanacearum are discussed. Proteomic of temperature stress on expression of Piper yellow mottle virus infection and a management strategy in the field are discussed.